Effects of Hunger on Visual Perception in Binocular Rivalry - Weng, Xin; Lin, Qi; Ma, Ye; Peng, Yu; Hu, Yang; Zhou, Ke; Shen, Fengtao; Wang, Huimin; Wang, Zhaoxin (Frontiers in Psychology, 2019)
The effect of hunger on visual perception is largely absent from contemporary vision science. Using a well-established visual phenomenon termed binocular rivalry, this study was carried out to investigate the effects of hunger on visual perception. A within-subject design was applied, in which participants attended two sessions before and after their lunch or dinner, i.e., a hunger state and a satiated state. In Experiment 1, we found that the mean dominance times to food-related pictures were larger in the hungry condition than that in the satiated condition, while the mean dominances time to the non-food stimuli were unaffected. In Experiment 2, we found the times to break through continuous flash suppression (b-CFS) for both food-related and non-food-related pictures were not affected by hunger. In Experiment 3, a probe-detection task was conducted to address possible response-biases. Our findings provide evidence that hunger biases the dynamic process of binocular rivalry to unsuppressed and visible food stimuli, while processing suppressed and invisible food-related was unaffected. Our results support the notion that the top-down modulation by hunger on food-related visual perception is limited to visible stimuli.